2016
DOI: 10.1088/1475-7516/2016/02/027
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate accelerated solutions as generic late-time attractors in a modified Jordan-Brans-Dicke theory

Abstract: In this paper we investigate the evolution of a Jordan-Brans-Dicke scalar field, Φ, with a power-law potential in the presence of a second scalar field, φ, with an exponential potential, in both the Jordan and the Einstein frames. We present the relation of our model with the induced gravity model with power-law potential and the integrability of this kind of models is discussed when the quintessence field φ is massless, and has a small velocity. The fact that for some fine-tuned values of the parameters we ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 113 publications
1
23
0
Order By: Relevance
“…In one sector of the present work, we would like to consider warm tachyon model on the brane in the context of "intermediate inflation". This scenario is one of the exact solutions of inflationary field equation in the Einstein theory with scale factor a(t) = a 0 exp(At f ) (A > 0, 0 < f < 1), this solution of the scale factor in the context of a modified tensor-scalar theory has been found in [33]. The study of this model is motivated by string/M-theory [34].…”
Section: Introductionmentioning
confidence: 88%
“…In one sector of the present work, we would like to consider warm tachyon model on the brane in the context of "intermediate inflation". This scenario is one of the exact solutions of inflationary field equation in the Einstein theory with scale factor a(t) = a 0 exp(At f ) (A > 0, 0 < f < 1), this solution of the scale factor in the context of a modified tensor-scalar theory has been found in [33]. The study of this model is motivated by string/M-theory [34].…”
Section: Introductionmentioning
confidence: 88%
“…The presence of a non-trivial matter field can change the features of the late time asymptotics. For example, Cid et al (2016) showed that in the case of the presence of a second, minimally coupled scalar field one can prove that a de Sitter solution is not the asymptotic state for the cosmological model.…”
Section: Brans-dicke Theorymentioning
confidence: 99%
“…The latter system has been the case of study of various analysis in the literature [49][50][51][52][53][54][55][56][57][58][59][60] where Q = Q (ρ m , ρ d ) has been assumed to be either a linear function [46][47][48][49][61][62][63][64][65][66] and many others. Additionally, with the above choices for the coupling function, various functional forms of the scalar field potential function V (φ) can also be chosen [33,35,[50][51][52]60,[67][68][69][70][71][72].…”
Section: Interacting Dark Energymentioning
confidence: 99%